A new species of Tropidophorus Duméril & Bibron, 1839 (Squamata: Sauria: Scincidae) from Sarawak, East Malaysia (Borneo) - Yong, Min pui; Benjamin, Karin; Bauer, Aaron M.; Das, I. (Zootaxa, 2017)
A new species of the genus Tropidophorus is described from Putai, upper Baleh, Kapit districts, Sarawak, East Malaysia (Borneo). Tropidophorus sebi sp. nov. is diagnosable from congeners from Borneo by the combination of the following characters: head shields present, dorsal and lateral scales smooth; parietal scales in two pairs; supraciliaries eight; supraoculars four; supralabials seven; infralabials four; postmental undivided; longitudinal scale rows 58; ventrals 53; transverse scale rows at midbody 34; subcaudals 98; preanals enlarged, single; and subdigital lamellae of Toe IV 19. In addition, we determine the phylogenetic position of this species within the Tropidophorus group based on mitochondrial markers, and present a key to identification of the known Bornean species in the genus.